The Role of PAI Teachers in Preventing Juvenile Delinquency Behavior - Maulana, Dessy; Supratman Zakir (BiCED Proceeding, 2024)
The purpose of this research is to find out how PAI teachers stop students from committing juvenile offenses. Learners who commit juvenile delinquency at school are the inspiration for this research. We know that teenagers are still unstable, lose direction in making decisions, and get angry easily when solving problems. Therefore, the task of PAI teachers is to deal with the problem of student delinquency by applying discipline. This research uses a qualitative method and conducts a literature study by analyzing various literature from books and journals.The results of the author's research resulted in several important conclusions. First, student delinquent behavior consists of violations of school rules, teaching-learning activities, school order, and social norms in the school environment. Second, the causes of delinquent behavior consist of internal factors of the students themselves and external factors, especially in terms of social interaction at school. The role of Islamic religious education teachers is prevention, curative handling and special handling includes taking a special approach to each case.